2018
DOI: 10.1093/conphys/coy002
|View full text |Cite
|
Sign up to set email alerts
|

Conservation choice on the rare endangered plants Glehnia littoralis

Abstract: Inland cultivation caused declines of buoyancy and germination ability of Glehnia littoralis fruits, because of long-term dispersal failure. Inland transplanting is, therefore, insufficient for conserving this species. As a coastal specialist, G. littoralis can only persist for long along sand coasts, where storm surge is a natural vector for dispersal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Secondly, the destruction of beach habitats by human factors, such as excessive excavation and coastal development, is another possible reason for the decline of G. littoralis, as reported previously [51,55,59]. Human domestication and cultivation can avoid the influences of the above adverse environmental factors, but Pan et al [60] found that the cultivated G. littoralis have experienced significant declines relative to the wild ones, and human cultivation was believed to be insufficient for conserving G. littoralis. Based on the above findings, we suggest that the conservation strategy for G. littoralis should include the protection of all the original populations to the extent possible.…”
Section: Cluster Analysis Results Revealed By Its and Rapdmentioning
confidence: 85%
“…Secondly, the destruction of beach habitats by human factors, such as excessive excavation and coastal development, is another possible reason for the decline of G. littoralis, as reported previously [51,55,59]. Human domestication and cultivation can avoid the influences of the above adverse environmental factors, but Pan et al [60] found that the cultivated G. littoralis have experienced significant declines relative to the wild ones, and human cultivation was believed to be insufficient for conserving G. littoralis. Based on the above findings, we suggest that the conservation strategy for G. littoralis should include the protection of all the original populations to the extent possible.…”
Section: Cluster Analysis Results Revealed By Its and Rapdmentioning
confidence: 85%
“…simplicifolia Cham. (Yang et al 2012), suggesting that the seeds of G. littoralis have the potential for dispersal via sea currents (Pang et al 2018). In addition to buoyancy of the diaspores, the longevity of seeds during seed flow is inevitable for the accomplishment of long-distance gene flow (Alafeh and Kadereit 2006).…”
Section: Discussionmentioning
confidence: 99%
“… Yanxia Pan and colleagues (2018) compared the cultivated plant to its wild relatives to find how it had changed since domestication. They wanted to know how buoyant the seeds were in seawater and how well they germinated after immersion.…”
mentioning
confidence: 99%